2018
DOI: 10.3390/antiox7010012
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E as a Treatment for Nonalcoholic Fatty Liver Disease: Reality or Myth?

Abstract: Obesity is one of the major epidemics of this millennium, and its incidence is growing worldwide. Following the epidemics of obesity, nonalcoholic fatty liver disease (NAFLD) has become a disease of increasing prevalence and a leading cause of morbidity and mortality closely related to cardiovascular disease, malignancies, and cirrhosis. It is believed that oxidative stress is a main player in the development and progression of NAFLD. Currently, a pharmacological approach has become necessary in NAFLD because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 75 publications
2
64
0
3
Order By: Relevance
“…This paper comes back to the initial discovery of vitamin E in 1922 as a substance necessary for reproduction. El Hadi et al [ 10 ] discuss vitamin E as a potent antioxidant being able to reduce oxidative stress in nonalcoholic fatty liver disease. They also present therapeutic efficacy.…”
mentioning
confidence: 99%
“…This paper comes back to the initial discovery of vitamin E in 1922 as a substance necessary for reproduction. El Hadi et al [ 10 ] discuss vitamin E as a potent antioxidant being able to reduce oxidative stress in nonalcoholic fatty liver disease. They also present therapeutic efficacy.…”
mentioning
confidence: 99%
“…A randomized three arm controlled trial (PIVENS) conducted by Sanyal AJ et al, on 247 patients who received vitamin E 800 IU once daily for the period of 96 weeks in one arm showed reduction in AST and ALT levels by 21.3 IU/L and 37 IU/L respectively [5]. Open Journal of Gastroenterology excellent anti-oxidant and help in neutralizing reactive oxygen species generated due to disturbed metabolism [10] [11]. A meta-analysis of randomized controlled trials conducted by Sato K, et al; found vitamin E significantly improved liver function and histologic changes in patients with NAFLD/NASH.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by meta-analyses of clinical trials, where vitE has been shown to decrease aminotransferase levels (hepatic injury enzymes), improve steatosis, lobular inflammation, ballooning hepatocytes, and to be effective in the overall resolution of steatohepatitis [28,29]. Additional mechanisms of vitE supplementation have been proposed, including regulation of the inflammatory response, cell proliferation and regulation of the expression of target genes coupled to the formation of hepatic damage in NASH [30,31]. VitE putatively possesses the ability to inhibit the activity of protein kinase C, resulting in reduced proliferation and adhesion of various cell types, including monocytes/macrophages and neutrophils hallmarking NASH, as well as fibroblasts involved in the deposition of extracellular fibrosis [11,30,31].…”
Section: Introductionmentioning
confidence: 98%